Lagrangian Mechanics - Canbolat, Hüseyin (IntechOpen, 2017)
Lagrangian mechanics is widely used in several areas of research and technology. It is simply a reformulation of the classical mechanics by the mathematician and astronomer Joseph-Louis Lagrange in 1788. Since then, this approach has been applied to various fields. In this book, the section authors provide state-of-the-art research studies on Lagrangian mechanics. Hopefully, the researchers will benefit from the book in conducting their studies.